Answer:
56
Step-by-step explanation:
The angle sum theorem *I think* is that for an n-sided shape, the total sum of its angles is 180(n-2).
The sum of a triangles' angles is 180 degrees.
Therefore 4v-44 = 180.
v - 11 = 45
v = 56 degrees
Note: always check if the answer makes sense
Let b>a,
a+b=40 so we can say a=40-b
We are told that b-a=6.5, using a found above in the equation gives us:
b-(40-b)=6.5
b-40+b=6.5
2b-40=6.5
2b=46.5
b=23.25, and since a=40-b
a=40-23.25
a=16.75
So a=16.75 and b=23.25
check...
16.75+23.25=40, 40=40
23.25-16.75=6.5, 6.5=6.5
Answer:
x = 38, y = 4
Step-by-step explanation:
Since AB = BC then the triangle is isosceles and the base angles are congruent, that is
∠ DAB = ∠ DCB = 52°
Subtract the sum of the base angle from 180° for ∠ ABC
∠ ABC = 180° - (52 + 52)° = 180° - 104° = 76°
Note that ∠ ABD = ∠ CBD, thus
x = 76 ÷ 2 = 38
BD bisects the side AC, thus DC = AD = 4
Thus y = 4
Answer:
22x -21
Step-by-step explanation:
(3x + 14) + (19x - 35)
Combine like terms
3x+19x + 14-35
22x -21